How is Calderón’s "La dama duende" built - Bobes Naves, María del Carmen (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
Dramatic text is characterized by the objetived forms and the modes of reception, contrasting with the narration and the lyric poem. The present analysis studies how the dialoged speech of the dramatic work builds the spaces of the plot taking into account a scenic space, i. e. a type of theater. The Spanish theater writes its texts for the stage thought for the corral de comedias. La dama duende organizes its spectacular text starting from a divided scenery containing a latent space and other patent one separated by a glass cupboard, available for some characters and no for others. This division of the scenery favours the layout of the plot in a specular form, in such a way that both the situations and the characters are parallel.